Economical -geographic problems of the development of the Karaganda agglomeration (Journal of Geography and Environmental Management, 2019)
This article considers the problem of the spatial organization of Central-Kazakhstan region. The results shows in theconditions of our country is brought to the forefront the task of a comprehensive and harmonious development of theKaraganda agglomeration, and elaboration of effective transformation of the socio-economic space of the region.